Computational modeling and experimental investigation of effects of compositional elements on interface and design aesthetics - Bauerly, Michael; Liu, Yili (International journal of human-computer studies, 2006)
This article describes computational modeling and two corresponding experimental investigations of the effects of symmetry, balance and quantity of construction elements on interface aesthetic judgments. In the first experiment, 30 black and white geometric images were developed by systematically varying these three attributes in order to validate computational aesthetic quantification algorithms with subject ratings. The second experiment employed the same image layout as Experiment 1 but with realistic looking web pages as stimuli. The images were rated by 16 subjects in each experiment using the ratio-scale magnitude estimation method against a benchmark image with average balance and symmetry values and a standard number of elements. Subjects also established an ordered list of the images according to their aesthetic appeal using the Balanced-Incomplete-Block (BIB) ranking method. Results from both experiments show that subjects are adept at judging symmetry and balance in both the horizontal and vertical directions and thus the quantification of those attributes is justified. The first experiment establishes a relationship between a higher symmetry value and aesthetic appeal for the basic imagery showing that subjects preferred symmetric over non-symmetric images. The second experiment illustrates that increasing the number of groups in a web page causes a decrease in the aesthetic appeal rating.